The Persistent Challenge of Pneumocystis Growth Outside the Mammalian Lung: Past and Future Approaches - Cushion, Melanie T.; Tisdale-Macioce, Nikeya; Sayson, Steven G.; Porollo, Aleksey (Frontiers in Microbiology, 2021)
The pathogenic fungi in the genus, Pneumocystis, have eluded attempts to continuously grow them in an ex vivo cultivation system. New data from transcriptomic and genomic sequencing studies have identified a myriad of absent metabolic pathways, helping to define their host obligate nature. These nutrients, factors, and co-factors are acquired from their mammalian host and provide clues to further supplementation of existing media formulations. Likewise, a new appreciation of the pivotal role for the sexual cycle in the survival and dissemination of the infection suggests that Pneumocystis species are obligated to undergo mating and sexual reproduction in their life cycle with a questionable role for an asexual cycle. The lack of ascus formation in any previous cultivation attempts may explain the failure to identify a sustainable system. Many characteristics of these ascomycetes suggest a biotrophic existence within the lungs of the mammalian hosts. In the present review, previous attempts at growing these fungi ex vivo are summarized. The significance of their life cycle is considered, and a list of potential supplements based on the genomic and transcriptomic studies is presented. State of the art technologies such as metabolomics, organoids, and air lift cultures are discussed as potential growth systems.